Constitutional visions of the World Trade Organization: between development, the free market, and marginality. The case of Colombia - Parra Rosas, Juan Felipe; Cumbe Figueroa, Alexandra; Jaramillo Vargas, Diego Andres (Latin American Journal of Trade Policy, 2023)
This article analyzes the background rule used by the Colombian Constitutional Court when it mentions and operates the World Trade Organization (WTO) sources in its rulings. We examined in the light of two conceptual frameworks: "the Synthesis of the 20th Century" and the "fundamental rules that condition the resolution of a case." To do this, through the jurisprudential review methodology, we analyzed 60 constitutionality rulings handed down by the Colombian Constitutional Court between 1995 and 2022, in which there was a direct mention of the WTO. Within this search, we found that of the 60 rulings, only 19 mention the WTO in their central reasoning or use some of its sources or regulatory considerations to support the decisions made. In our findings, we find that the mention of the WTO is used by the Court to justify and constitutionally support the free market that, under the premise of an absence of exercises of power, is understood as an economic project that promotes and strengthens social and economic development of the States.